Penerapan Akupresur dalam Menurunkan Hipertensi pada Lansia di Wilayah Kerja Puskesmas Grabag - Rani Febriyanti; Maryatun Maryatun (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Hypertension is commonly referred to as high blood pressure. A person has hypertension if his systolic and diastolic blood pressure has risen above 140/90 mmHg. Hypertension is the leading cause of premature death worldwide with more than 1 in 4 men and 1 in 5 women and more than one billion people experiencing the condition (WHO, 2020). Non-pharmacological therapy acupressure therapy can be an option for the elderly to overcome hypertension. Objective: To describe the results of the comparison of blood pressure reduction in the elderly before and after the application of acupressure therapy on 2 (two) respondents. Methods: This study uses a descriptive method, selecting samples according to the inclusion criteria and selecting 2 elderly respondents who experience hypertension. The research instrument used a digital Sphygmomanometer and the research was carried out 15 minutes for 3 consecutive days. Results: There was a decrease in systolic pressure in Mrs. T by 10 mmHg and a decrease in Mrs. P's systolic pressure by 7 mmHg. While the diastolic pressure of Mrs. T was 12 mmHg and Mrs. P decreased by 10 mmHg. The results of the application of acupressure therapy on both respondents showed a change in blood pressure reduction from previously included in the classification of grade 1 hypertension to high normal. Conclusion: There are differences before and after acupressure in elderly hypertension.